Implementation of Islamic Religious Education Learning in the Class VII Merdeka Curriculum - Khasanah, Irma Nur; Kurniawan, Muh. Alif; Madjid, Abdul; Fatiatun, Fatiatun (Universitas Ahmad Dahlan, 2023)
Changing the new curriculum is a particular concern in educational institutions because of the need for new adaptations to all new things. It is not impossible to do, but being able to adapt to new changes requires a process to achieve the best. Implementing learning with the new curriculum also requires all parties to continue learning so they can adapt to existing conditions and circumstances and all of this is not instantaneous. The aim of this research is to provide an overview of the application of Islamic religious education learning in the independent curriculum. This research uses a descriptive qualitative research method with a field study approach. This research leads to direct field observations with the subject of school principals and Islamic religious education teachers. The power collection techniques used include observation, interviews and documentation. This research is supported by data analysis, namely data reduction, data presentation and drawing conclusions. The results of this research show that the implementation of Islamic religious education learning in the independent curriculum has several stages, including the planning stage, implementation stage and evaluation stage.